2019
DOI: 10.1111/and.13340
|View full text |Cite
|
Sign up to set email alerts
|

IMSI procedure improves clinical outcomes and embryo morphokinetics in patients with different aetiologies of male infertility

Abstract: Our objective was to evaluate the effect of IMSI on embryo kinetics and clinical outcomes in patients with different aetiologies of male infertility. A total of 150 couples with different aetiologies of male infertility were randomly divided into ICSI and IMSI treatment groups (n = 75). ICSI was done accordingly. For IMSI group, the sperm selection was done using MSOME criteria and then injected. The zygotes were cultured in time‐lapse monitoring system (TLM) for 3 days. A total of 650 embryos were developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…Our results were different from other studies (Mangoli et al., 2019, 2020). It was noted that sperm selection through ICSI led to the delay of S1, T4, S2 and T5 in embryos of infertile men diagnosed with oligoasthenoteratozoospermia when compared to other aetiologies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results were different from other studies (Mangoli et al., 2019, 2020). It was noted that sperm selection through ICSI led to the delay of S1, T4, S2 and T5 in embryos of infertile men diagnosed with oligoasthenoteratozoospermia when compared to other aetiologies.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, our study is the first to answer the raising question whether the two sperm selection modalities influence embryo morphokinetics as well as reduce the incidence of anomaly development derived from sub‐optimal spermatozoa upon the blastocyst stage, while two studies have investigated until the cleavage stage (day 3) (Mangoli et al., 2019, 2020). Differences between three kinetic time points (T7, TEB and CC3) of IMSI‐ and ICSI‐derived embryos were apparent while other morphokinetic parameters did not differ between the two sperm selection methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the motile sperm organelle morphology examination (MSOME) technique, in a series of 10 patients with teratozoospermia, Knez et al 7 demonstrated that head vacuoles of injected spermatozoa affect morphokinetic parameters and implantation rates. In another study published recently, 8 embryos of OAT patients exhibited protracted developmental dynamics compared to other sperm pathologies—asthenozoospermia, asthenoteratozoospermia, and teratozoospermia.…”
Section: Introductionmentioning
confidence: 90%
“…Combination of morphological and morphokinetic parameters can assist in selecting the embryos with high implantation potential. Time‐laps monitoring (TLM) is a predicting tool for evaluating embryos with higher development potential, implantation and even embryo aneuploidy status (Faramarzi, Khalili, & Jahromi, 2019; Mangoli et al., 2019; Omidi, Khalili, Halvaei, Montazeri, & Kalantar, 2020). This technology allows investigation of embryo development in stable incubator condition (Bhide et al., 2017).…”
Section: Introductionmentioning
confidence: 99%